Understanding teacher supply: Where do online Initial Teacher Education students fit?. (April 2017) - Edwards, Daniel; Weldon, Paul
Curriculum delivery in higher education is changing rapidly, notably in the area of online delivery. Initial Teacher Education (ITE) in Australia is no exception to this, and this article explores this growth with a particular focus on its implications for workforce planning for teachers. In this planning in Australia, ITE students are usually considered part of the 'supply pipeline' for the state in which their university is located. However, with online delivery, students could potentially be enrolled on the other side of the country (or the world) from the physical location of their institution. The data presented here show that of the growing cohort of external ITE graduates, a small but significant group resides outside of the state in which their institution of enrolment is located. This exploration of data highlights some new evidence which has consequences for teacher supply planning and offers insight to inform future teacher workforce projections.